Kinematic of the sausage-feeder with crank mechanism - Nguyen , Hong Ngan (Journal of Technical Education Science, 2021)
The sausage feeder takes an important role in automatic packaging systems. This paper presents the theoretical calculation, kinematic characteristics of an automatic sausage feeder using vibration technique and crank mechanism. The kinematics formulation of the crank mechanism is done using vector loop method and cosine rule are applied to describe the position of the mechanisms. Velocity of crank and connecting rod is performed by differentiating the position in terms of following crank angle and connecting rod angle respectively. The acceleration equation is derived from the velocity in the same principle. Based on the kinematics, equations of the crank mechanism motion, components are formulated for each moving link and platform then, all motion parameters of each component about its crank angle are readily derivedand the interaction of the sausage with mechanism was built. Furthermore, the 2D models are provided by using 2D Auto CAD software to visualize the system and mathematical algorithm solved by using software MATLAB-SIMULINK.